Analisis Unsur Intrinsik Dalam Kumpulan Cerita Rakyat Berupa Dongeng Sunda - Kurniasih; Koswara, Dedi (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2024)
This research was motivated by the lack of public attention and concern in preserving folklore passed down by their ancestors, especially Sundanese fairy tales. This research aims to describe the intrinsic elements which include: theme, plot, characterization, setting, message and point of view of the fairy tale. This study used descriptive qualitative method. The data source for this research is a collection of famous Sundanese fairy tales from West Java. The results of the research show that there is the same major theme in which the fairy tales studied carry the theme of life. The plot of each fairy tale is divided into exposition, complication and resolution (advanced and mixed plot). Characterization includes characters, characters and the way the characters are conveyed. The point of view conveyed by the three fairy tales is the same, namely, the point of view of the third person or the author as narrator. Most fairy tale settings take place in a village, a royal palace and a forest. Every fairy tale contains a message that is conveyed either explicitly or implicitly. These three fairy tales are included in the classic fairy tale category.